PENERAPAN PENDEKATAN STEM PADA MATERI PENYARINGAN AIR UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD - Rahmadani, Sonia; Yumna; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science learning outcomes of fourth-grade students. at SDN 16 Lubuak Tarok on the topic of simple water filtration. Learning activities were still dominated by conventional teaching methods which made students less active and had difficulty understanding scientific concepts. This study aimed to improve students' science learning outcomes through the implementation of the Science, Technology, Engineering, and Mathematics (STEM) approach. This study used Classroom Action Research (PTK) conducted in two cycles consisting of planning, action, observation, and reflection stages. The research subjects were 11 fourth grade students of SDN 16 Lubuak Tarok. Data were collected through learning outcome tests, observation sheets, and documentation. Data analysis used both quantitative and qualitative techniques. The results showed that the implementation of the STEM approach improved students’ learning outcomes. In cycle I, the average score was 80,5 with a learning completeness percentage of 72.73% (8 students completed). After improvements in cycle II, the average score increased to 95 with a completeness percentage of 100% (11 students completed). The findings indicate that the STEM approach can effectively improve students' understanding through experimental activities, problem-solving, and designing simple technology related to real-life situations. Therefore, the STEM approach can be used as an effective learning strategy to improve science learning outcomes in elementary schools.